Are Moderate and Vigorous Leisure-Time Physical Activity Associated With Musculoskeletal Pain? A Cross-Sectional Study Among 981 Physical Therapists. Issue 1 (January 2020) - Ezzatvar, Y.; Calatayud, J.; Andersen, L.L.; Casaña, J.
Purpose: Musculoskeletal pain (MP) is common among workers, especially for health-care professionals. Paradoxically, many of those rehabilitating patients for pain—that is, physical therapists (PTs)—also have pain. Adequate levels of physical activity are recommended for cardiovascular and musculoskeletal health. However, the association between physical activity and MP among PTs remains unknown. This study aims to determine the association between moderate and vigorous leisure-time physical activity levels and MP in PTs. Design: Cross-sectional study. Setting: Workplace. Participants: Nine hundred eighty-one PTs. Measures: Data on MP and leisure-time physical activity were collected using an online survey. Analysis: The odds for having lower level of MP as a function of physical activity were estimated using binary logistic regression controlled for various confounders. Results: Performing ≥75 min/week of vigorous leisure-time physical activity increased the odds of experiencing lower levels of neck–shoulder pain (odds ratio = 1.43, 95% confidence interval, 1.05-1.94). No association was found neither between vigorous nor between moderate leisure-time physical activity and MP in the arm-hand or back. Conclusion: Performing ≥75 min/week of vigorous leisure-time physical activity is associated with lower levels of MP in neck and shoulders among PTs. No associations were found between vigorous or moderate leisure-time physical activity and MP in arm-hand and back.